Helicobacter pylori infection among dyspeptic patients in Chitwan, Nepal - Chaudhary, Navin Kumar; Paudel, Sukrat (Journal of Chitwan Medical College, 2021)
Background: Helicobacter pylori are gram-negative bacillus that colonizes the gastrointestinal mucosa. Dyspepsia is a clinical syndrome including manifestations related to the upper gastrointestinal tract, which may include acute, chronic, or recurrent pain or discomfort. Understanding the prevalence and the factors associated with H. pylori seropositivity in dyspeptic persons can provide a guide for health policies. Aim of the research was to study the prevalence and factors associated with H. pylori infection among dyspeptic patients in Chitwan, Nepal. Methods: A descriptive cross-sectional study was conducted in the Department of Microbiology at CMC-TH from July 2019 to June 2021. A non-probability consecutive sampling technique was employed to collect 510 Stool samples from the suspected patients for the detection of H. pylori stool antigen (HpSAg) following the procedures recommended by the manufacturer. A standard questionnaire on the potential risk factors was also designated and completed. Chi-square test was used to study the association of H. pylori colonization with symptoms, life-style findings and socio-economic status. p<0.05 were considered statistically significant. Results: HpSAg was detected in 20.0%. Prevalence was higher (25.0%) among males compared to females (15.56%). Prevalence was higher among middle-aged (21-60 years) people with smoking, alcohol, and tobacco consumption habits. Socioeconomic conditions and family size play an important role in the prevalence. Nausea, sour eructation, bloating, heartburn, and bleaching were the common symptoms among dyspeptic patients. Conclusions: The burden of H. pylori infection in patients with dyspepsia was high. Factors associated with an elevated level of colonization by H. pylori leading to dyspepsia are low income, education up to the primary, habits like smoking, alcohol, and tobacco consumption.